Human Rights and Democracy The Precarious Triumph of Ideals - Landman, Todd (Bloomsbury Academic, 2013)
Combines an overview of the key theoretical models of democracy and human rights with a state-of-the-art survey which reports on trade-offs between achievements, set-backs and challenges in some of the world's 'hotspots'. The 20th century has been described as the bloodiest in human history, but it was also the century in which people around the world embraced ideas of democracy and human rights as never before, constructing social, political and legal institutions seeking to contain human behaviour. Todd Landman offers an optimistic, yet cautionary tale of these developments, drawing on the literature, from politics, international relations and international law. He celebrates the global turn from tyranny and violence towards democracy and rights but also warns of the precariousness of these achievements in the face of democratic setbacks and the undermining of rights commitments by many countries during the so-called 'War on Terror'.